A Deviant Tradition of Tile Stamping in the Roman North: The CA TI stamps on Roman roof tiles from Gallia Belgica in a broader context - Clerbaut, Tim (Rei Cretariae Romanae Fautorum Acta, 2017)
As part of an ongoing PhD-research on Roman ceramic building materials at Ghent University, the material of several sites in Gallia and Germania Inferior is studied in more detail taking into account various aspects of the available material evidence. One of these aspects is the study of the epigraphical evidence present such as brick and tile stamps. The tradition of stamping these products was introduced by the military in the region with the technique itself. Apart from military production, civil producers were present as well from the 2nd century onwards.